2009
DOI: 10.1016/j.still.2009.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Conservation tillage: Short- and long-term effects on soil carbon fractions and enzymatic activities under Mediterranean conditions

Abstract: Click here to download Manuscript: PAPER.doc Click here to view linked References term trial. In general, only the stratification ratios of AC were higher in CT than in TT in both trials. The results of this study showed that AC content was the most sensible and reliable indicator for assessing the impact of different soil management on soil quality in the two experiments (short-and long-term). Conservation management in dryland farming systems improved the quality of soil under our conditions, especially at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
80
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(93 citation statements)
references
References 32 publications
11
80
1
1
Order By: Relevance
“…This suggests a beneficial influence of the RT treatment on the soil environment in comparison with the CT treatment. It has been suggested that a ploughless tillage system creates a less oxidative biochemical environment than plough-based tillage and provides better protection and stabilization of SOM through the activity of microorganisms and soil enzymes (Melero et al, 2009(Melero et al, , 2011.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests a beneficial influence of the RT treatment on the soil environment in comparison with the CT treatment. It has been suggested that a ploughless tillage system creates a less oxidative biochemical environment than plough-based tillage and provides better protection and stabilization of SOM through the activity of microorganisms and soil enzymes (Melero et al, 2009(Melero et al, , 2011.…”
Section: Resultsmentioning
confidence: 99%
“…The largest increments were observed in the β-glucosidase enzyme. These results agreed with Melero et al (2009) and De la Horra et al (2003) which also found that due to the involvement of this enzyme with the transformation of organic matter, the superficial layer had higher β-glucosidase activity.…”
Section: Resultssupporting
confidence: 89%
“…Most of the correlations were found also in other long-term experiments (Acosta-Martinez et al, 2003;Balota et al, 2014a;Melero et al, 2009). The accumulation of organic matter in the upper soil layer by CC and minimum tillage, and also the contribution of the main crops (root exudates, decomposition of roots and crop residues) stimulated the microbial community and enhanced the enzymes activity (Balota et al, 2004).…”
Section: Resultssupporting
confidence: 69%
“…A similar result was obtained by Diekow et al, 2005. Franzluebbers andArshad (1996) and Melero et al (2009) suggest that minimum tillage can increase SOC under longer experimental duration. Our results are in agreement with this because in AC1 increased SOC stock and the LUC and tillage for the long term (46 years) reduced SOC stock.…”
Section: The Effect Of Luc On Soc Stock Tn and C : N Ratiomentioning
confidence: 98%
“…Therefore, C sequestration into soils is one of the most important ecosystem services because of its role in climate regulation (IPCC, 2007). Intensification of agriculture and/or transformation of conventional tillage (CT) practices, may cause enormous losses of soil organic carbon (SOC), thus inducing an increase in soil erosion and a breakage of soil structure (Melero et al, 2009). Land use change (LUC) is considered the second greatest cause of C emissions after fuel consumption (Watson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%